Revisiting Tversky's diagnosticity principle - Evers, Ellen R. K.; Lakens, Daniël (Frontiers in Psychology, 2014)
Similarity is a fundamental concept in cognition. In 1977 Amos Tversky published a highly influential feature-based model of how people judge the similarity between objects. The model highlights the context-dependence of similarity judgments, and challenged geometric models of similarity. One of the context-dependent effects Tversky describes is the diagnosticity principle. The diagnosticity principle determines which features are used to cluster multiple objects into subgroups. Perceived similarity between items within clusters is expected to increase, while similarity between items in different clusters decreases. Here, we present two pre-registered replications of the studies on the diagnosticity effect reported in Tversky, 1977. Additionally, one alternative mechanism that has been proposed to play a role in the original studies, an increase in the choice for distractor items (a substitution effect, see Medin, Goldstone, & Markman, 1995), is examined. Our results replicate those found by Tversky (1977) finding an average diagnosticity-effect of 4.75%. However, when we eliminate the possibility of substitution effects confounding the results, the data provide no indication of any remaining effect of diagnosticity (0.41%, n.s.).